Nitrogen and phosphorus requirement of winged bean (Psophocarpus tetragonolobus (L.) DC.) in Oxisol and Ultisol - Chulan, Azizah; Omar, Mohammed; Hall, I. R. (Malaysian Society of Applied Biology, 1986)
The response of winged bean (Psoph ocarpus tetragonolobus) to 6 different soil P levels and 3 different soil N levels were compared in two soil types (an Oxisol and an Ultisol) for a period of 4 months. Moderate applications of N and P fertilizers (i.e. 14 kg N/ha and 13 kg P/ha) were found to be optimum for maximum plant growth in the Serdang soil. However. Munchong soils were found to support just as much growth as Serdang when higher levels of P were applied